2019
DOI: 10.2106/jbjs.18.01467
|View full text |Cite
|
Sign up to set email alerts
|

Graft Diameter and Graft Type as Predictors of Anterior Cruciate Ligament Revision

Abstract: Background: It is important to investigate and compare graft diameters as well as graft types to identify risk factors for revision after an anterior cruciate ligament (ACL) reconstruction. We performed the current study in order to analyze the early ACL revision rate among patients treated with hamstring tendon (HT) autografts or patellar tendon (PT) autografts of different diameters. Our hypothesis was that an increase in both HT and PT autograft diameters would reduce the risk of early ACL revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 37 publications
0
61
2
Order By: Relevance
“…The hamstring graft diameter was reported to predict graft failure. A graft diameter less than 8 mm increased the failure rate [13,33]. However, in a recent study by Inderhaug, graft diameter was not found to be a risk factor for ACL revision surgery [34], nor did the present study confirm the association between graft diameter and revision rate.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The hamstring graft diameter was reported to predict graft failure. A graft diameter less than 8 mm increased the failure rate [13,33]. However, in a recent study by Inderhaug, graft diameter was not found to be a risk factor for ACL revision surgery [34], nor did the present study confirm the association between graft diameter and revision rate.…”
Section: Discussioncontrasting
confidence: 75%
“…A smaller graft size may contribute to a higher risk of graft rupture. Snaebjörnsson et al found a correlation in adults between graft diameter and revision rates [13], but this has not yet been clarified in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…In a Norwegian population of high-level athletes competing in handball, soccer and alpine skiing, the risk of graft revision J o u r n a l P r e -p r o o f was 2.8 times higher in individuals younger than 18 years undergoing ACL reconstruction with HT compared to BTB autograft [82]. Studies from the Swedish National Knee Ligament Registry identified that diminishing HT graft diameter in 0.5 mm increments increases the risk of revision surgery, [83] and HT graft diameters smaller than 8 mm have significantly greater risk of failure than those 8 mm and larger [79].…”
Section: Randomized Control Studies Comparing Anatomic Acl Reconstruc...mentioning
confidence: 98%
“…Amidst the several available graft options for anatomic ACL reconstruction, large-scale national registry studies comparing surgical outcomes between graft types have not produced a clear consensus regarding the superiority of one particular autograft over others [75][76][77][78][79][80]. The majority of registry studies comparing HT and bone-patellar tendon-bone (BTB) autografts have reported a higher relative risk of revision in the HT group [75,77,81].…”
Section: Randomized Control Studies Comparing Anatomic Acl Reconstruc...mentioning
confidence: 99%
“…15 A recent study from the Swedish and Norwegian National Knee Ligament Registries reported that hamstring autograft ACL reconstruction patients with grafts 9 mm in diameter or greater had equal results to patellar tendon autograft ACL reconstruction patients. 16 The authors should be commended for obtaining minimum graft diameters of 9 mm in their autograft patients. My experience would suggest that this should not be expected in all hamstring autograft patients.…”
Section: See Related Article On Page 3140mentioning
confidence: 99%